Culturally competent family therapy : a general model - Ariel, Shlomo (Contributions in psychology, 1999)
A guide to a therapy which incorporates the cultural issues contributing to the problems which families of any sociocultural background may face. It covers difficulties such as intermarriage, immigration, acculturation, socioeconomic inequality, prejudice, and ecological or demographic change.